2019
DOI: 10.1007/s40495-019-00206-4
|View full text |Cite
|
Sign up to set email alerts
|

The Human Gut Microbiome’s Influence on Arsenic Toxicity

Abstract: Purpose of Review Arsenic exposure is a public health concern of global proportions with a high degree of interindividual variability in pathologic outcomes. Arsenic metabolism is a key factor underlying toxicity, and the primary purpose of this review is to summarize recent discoveries concerning the influence of the human gut microbiome on the metabolism, bioavailability, and toxicity of ingested arsenic. We review and discuss the current state of knowledge along with relevant methodologies for studying thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 131 publications
(144 reference statements)
0
20
0
Order By: Relevance
“…The effect of direct arsenic exposure on gut microbiome was studied before. [ 61 ] In six week old infants, 8 genera from Firmicutes phylum and 15 genera from other phyla were positively or negatively correlated with urinary arsenic levels. [ 62 ] Arsenic treatment also changed the taxonomic profile of the microbiome in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of direct arsenic exposure on gut microbiome was studied before. [ 61 ] In six week old infants, 8 genera from Firmicutes phylum and 15 genera from other phyla were positively or negatively correlated with urinary arsenic levels. [ 62 ] Arsenic treatment also changed the taxonomic profile of the microbiome in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…The ENS is innervated with extrinsic ANS (parasympathetic and sympathetic systems) [ 110 ]. The alteration of microbial communities at the gut epithelial barrier modulate both inflammatory responses and metabolic pathways [ 111 , 112 ].…”
Section: Microbiome–gut–brain Communication In Health and Diseasementioning
confidence: 99%
“…7 Report showed that the human gut microbiome may biochemically change the arsenic compounds, and several arsenical transformations by bacteria may lead to arsenic toxicity to the host. 8 Arsenic exposure is common through arsenic contaminated water and food, leading to disturbance in gut microbial activities. Microbiome composition and diversity in the gastrointestinal tract (GIT) vary, with individuals playing an essential role in determining the initial fate, mobility and relative toxicity of arsenic, whether inhaled or ingested.…”
Section: Introductionmentioning
confidence: 99%